Global solvability of systems on compact surfaces - Zugliani, Giuliano Angelo (2014)
We are interested in studying an involutive system defined by a closed non-exact 1-form on a closed and orientable surface. Here we present a necessary condition for the global solvability of this system. We also make some particular constructions of globally solvable systems that motivate the equivalence between the global solvability and the necessary condition, for two cases involving 1-forms of the Morse type, namely, when the surface is the bitorus or when the 1-form is generic